Legal consequences of breaking a marriage promise according to Indonesian civil law - Pongolingo, Sri Rahayu Ningsih (Journal of Law Science, 2024)
This paper examines the legal repercussions of a broken marriage vow under Indonesian civil law, concentrating on the aggrieved party's compensation rights. This study examines the Civil Code (KUHPerdata) and judicial precedents using normative legal research methodologies. Breaking a marriage pledge does not constitute a contract, although the injured party typically seeks compensation for substantive and immaterial damages. The harmed party commonly claims compensation under Article 1365 of the Civil Code on wrongful actions and breach of contract. The research found that although Indonesian civil law allows compensation, showing tangible and immaterial damages like damaged honor is difficult. Marriage commitments are typically handwritten and hard to establish in court. However, if the aggrieved party can establish a genuine loss, the court may protect them with a substantial and flexible approach. This research also emphasizes the need to enhance marriage promise laws and clarify evidence requirements to make civil law more responsive to societal changes.